Walkability indices and childhood obesity: A review of epidemiologic evidence. (27th July 2020) - Yang, Shujuan; Chen, Xiang; Wang, Lei; Wu, Tong; Fei, Teng; Xiao, Qian; Zhang, Gang; Ning, Yi; Jia, Peng
Summary: The lack of an active neighbourhood living environment can impact community health to a great extent. One such impact manifests in walkability, a measure of urban design in connecting places and facilitating physical activity. Although a low level of walkability is generally considered to be a risk factor for childhood obesity, this association has not been established in obesity research. To further examine this association, we conducted a literature search on PubMed, Web of Science and Scopus for articles published until 31 December 2018. The included literature examined the association between measures of walkability (e.g., walkability score and walkability index) and weight‐related behaviours and/or outcomes among children aged under 18 years. A total of 13 studies conducted in seven countries were identified, including 12 cross‐sectional studies and one longitudinal study. The sample size ranged from 98 to 37 460, with a mean of 4971 ± 10 618, and the age of samples ranged from 2 to 18. Eight studies reported that a higher level of walkability was associated with active lifestyles and healthy weight status, which was not supported by five studies. In addition to reviewing the state‐of‐the‐art of applications of walkability indices in childhood obesity studies, this study also provides guidance on when and how to use walkability indices in future obesity‐related research.